2010
DOI: 10.2527/jas.2009-1955
|View full text |Cite
|
Sign up to set email alerts
|

Expression of progesterone receptor related to the polymorphism in the PGR gene in the rabbit reproductive tract1

Abstract: The association of the 2464G > A SNP found in the promoter region of the rabbit progesterone receptor gene with progesterone receptor (PR) expression was evaluated by Western blot analysis. This SNP was associated with 2 lines divergently selected for uterine capacity, the high line selected to increase uterine capacity and the low line selected to decrease uterine capacity. Two progesterone isoforms were obtained using a commercial monoclonal antibody: the PR-B isoform described previously in rabbits, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
(33 reference statements)
1
21
0
1
Order By: Relevance
“…Although both PRA and PRB bind P4, several studies have shown that, depending on the cell and target genes, PRA and PRB have remarkably different transcriptional activities [31]. However, little information is available so far with respect to the respective roles of PRA and PRB in mediating P4 action in the mammalian oviduct [32,33]. Nevertheless, in the present study, nuclear P4 receptors were expressed between Day 1.5 and Day 5 post-ovulation in both the ampulla and the isthmus.…”
Section: Discussionmentioning
confidence: 99%
“…Although both PRA and PRB bind P4, several studies have shown that, depending on the cell and target genes, PRA and PRB have remarkably different transcriptional activities [31]. However, little information is available so far with respect to the respective roles of PRA and PRB in mediating P4 action in the mammalian oviduct [32,33]. Nevertheless, in the present study, nuclear P4 receptors were expressed between Day 1.5 and Day 5 post-ovulation in both the ampulla and the isthmus.…”
Section: Discussionmentioning
confidence: 99%
“…Les études de gènes candidats pour les caractères de reproduction sont toutes fondées sur une seule population expérimentale sélectionnée de façon divergente pour la capacité uté-rine (nombre maximal de foetus qu'une lapine peut porter lorsque le taux d'ovulation n'est pas facteur limitant) pendant 10 générations (Mocé et al, 2004). Une association entre le polymorphisme de trois gènes (OVGP1, PGR et TIMP1) et quelques caractères de reproduction, incluant l'implantation embryonnaire et la taille de portée, a été mise en évidence dans cette population expérimentale (Estellé et al, 2006 ;Peiró et al, 2008 ;Peiró et al, 2010 ;Argente et al, 2010 ;García et al, 2010).…”
Section: Caractères De Reproductionunclassified
“…As the main differences between lines appeared in the first two generations, the implication of at least one major gene affecting the UC and embryo survival was suggested (Argente et al 2003). Several studies of candidate genes for litter size and its components, such as embryo development or survival, have been performed in the both divergently selected lines (Estelle et al 2006;Merchán et al 2009;Argente et al 2010;García et al 2010;Peiró et al 2010). The main results of these studies 4 indicated that polymorphisms in tissue inhibitor of metalloproteinase-1 (TIMP-1), oviductal glycoprotein-1 (OVGP1) and progesterone receptor (PGR) are associated with the differences in embryo survival between H and L lines.…”
Section: Introductionmentioning
confidence: 99%
“…2B), although the L line presented more differentially expressed genes (UBC, SEP15, TCP1, CLU, HSD17B4 and PGR) than the H line (RPS20, RPS4X, ENV and OVGP1). Interestingly, the OVGP1 and the PGR genes has been previously selected as candidate genes to explain the differences in early embryo survival and development observed between the divergent rabbit lines selected for UC using an F2 population (García et al 2010;Peiró et al 2010).…”
Section: Ssh Librariesmentioning
confidence: 99%